Functional literacy, educational attainment and earnings: A multi-country comparison - Kevin J. Denny; Colm P. Harmon; Vincent O'Sullivan (University College Dublin, Department of Economics, 2003)
In this paper a rich and innovative dataset, the International Adult Literacy Survey, is used to examine the impact of functional literacy on earnings. We show that the estimated return to formal education is sensitive to the inclusion of literacy: excluding it biases the return to education in many countries by significant amounts. Literacy itself has a well-determined effect on earnings in all countries though with considerable variation in the size of the effect. The benefits of literacy do not only arise from increasing low levels of literacy: increases at already high levels generate substantial increases in earnings in some countries. In general we find little interaction between schooling and literacy though for a few countries they appear to complement each other.
hdl:10197/939
Keywords: 330